Prevalence and factors associated with vitamin D deficiency in systemic lupus erythematosus patients - Y Pangestu; S Setiati; Bambang Setiyohadi; N Sukmana (Indonesian Journal of Rheumatology, 2013)
Background: In addition to the calcium-phosphorus metabolism, vitamin D might also play a role in the immune system. Studies have showed lower levels of vitamin D among SLE patients compared with controls. Researches regarding vitamin D in SLE patients have only been conducted in four seasons’ countries (Caucasians subjects in a large part) , but no data has been available in tropical countries, particularly Indonesia. The presence of VDR gene polymorphism in different populations will affect the role of vitamin D in the immune system. Objectives: To determine the prevalence of vitamin D deficiency and identify its risk factors such as lack of sunlight exposure, sunscreen usage, long-term corticosteroid therapy, disease activity, insufficient vitamin D supplementation, and obesity in SLE patientswith vitamin D deficiency.Methods: A cross-sectional study was conducted on SLE patients who were under treatment at Cipto Mangunkusumo General Hospital or members of Indonesian Lupus Foundation. Then those patients completed questionnaires and their 25(OH)D serum levels were measured. The cut-off value of 25(OH) D levels for vitamin D inadequacy is 75 nmol/L, which then grouped into vitamin D insufficiency (25(OH)D 25 - <75 nmol/L) and vitamin D deficiency (25(OH)D <25 nmol/L). SLE activity was assessed with MEX-SLEDAI.Results: During May-June 2008, 80 SLE patients were enrolled with 96.3% female subjects, median age of 26 years (range 17-56 years), 66.3% non-obese, 93.8% using steroid, 62.5% with active disease, and 63.8%have adequate sun exposure. In addition, 81.5% didnot use sunscreen and 83.8% did not take vitamin D supplementation. All patients had vitamin D inadequacy with 41.2% in insufficiency level and the other 58.8% in deficiency level. The median of 25 (OH)D levels were 21.85 nmol/L (range 11.5-57.7 nmol/L). It also has been found that vitamin D deficiency occurred more in subjects who were obese, used sunscreens, had lower exposure to sunlight, in a long-term high-dose steroid therapy, had active SLE disease, and had no vitamin D supplements.Conclusions: All SLE patients had vitamin D inadequacy. Vitamin D deficiency occurred more in subjects who were obese, used sunscreens, had lower exposure to sunlight, in a long-term high-dose steroid therapy, had active SLE disease, and had no vitamin Dsupplements.